Hydraulic and Hemodynamic Performance of a Minimally Invasive Intra-arterial Right Ventricular Assist Device. Issue 9 (September 2014) - Hsu, Po-Lin; Graefe, Roland; Boehning, Fiete; Wu, Chen; Parker, Jack; Autschbach, Rüdiger; Schmitz-Rode, Thomas; Steinseifer, Ulrich
Right ventricular assistance is still in the early phase of development compared to left ventricular assist device (LVAD) technology. In order to provide flexible pulmonary support and potentially reduce the known complications, we propose a minimally invasive right ventricular assist device (MIRVAD), located in the pulmonary artery (PA) and operating in series with the right ventricle (RV). The MIRVAD is an intra-arterial rotary blood pump containing a single axial impeller, which is not enclosed by a rigid housing but stent-fixed within the vessel. The impeller geometry has been designed with the assistance of analytical methods and computational fluid dynamics (CFD). The hydraulic performance of the impeller was evaluated experimentally with a customized test setup using blood synthetic medium (HES). The blade-tip clearance (BTC) was varied between 0.25-4.25 mm to evaluate the effect of different PA sizes on impeller performance. Furthermore, the Langrangian particle-tracking method was used to estimate the level of hemolysis and generate numerical blood damage indexes. The impeller design generated 25.6 mmHg for flow rates of 5 lpm at a speed of 6, 000 rpm at the baseline condition, capable of providing sufficient support for the RV. The BTC presented a significant effect on the static pressure generation and the efficiency, but the operational range is suitable for most vessel sizes. The numerical results demonstrated a low risk of blood damage at the design point (mean Lagrangian damage index 2.6 * 10 -7 ). The preliminary results have encouraged further impeller optimization and development of the MIRVAD.